Endemic species of terrestrial isopods (Isopoda, Crustacea) in the Romanian fauna - Nicolae TOMESCU (Studia Universitatis Babeș-Bolyai. Biologia, 2018)
In the Romanian fauna 32 endemic species of terrestrial isopods were described; most of them are epigenous, few are troglobiont, troglophilous and edaphic species. Troglobiont species: Biharoniscus racovitzai, Biharoniscus fericeus, Haplophthalmus tismaniscus, Haplophtalmus caecus, Trachelipus troglobius. Troglophilous species: Trachelipus trilobatus, Hyloniscus flamuloides. Edaphic species: Trichoniscoides danubianus, Haplophtalmus napocensis, Haplophtalmus banaticus, Haplophtalmus medius, Haplophtalmus ionescui, Thaumatoniscellus orghidani. Epigenous species: Ligidium intermedium, Hyloniscus dacicus, Hyloniscus siculus, Hyloniscus motasi, Trichoniscus carpaticus, Haplophthalmus orientalis, Buddelundiella serbani, Trichorhina dobrogica, Platyarthrus dobrogicus, Cylisticus transsilvanicus, Cylisticus brachiurus, Porcellium transsylvanicum, Trachelipus ater, Trachelipus vareae, Trachelipus bujori, Trachelipus pleonglandulatus, Trachelipus spinulatus, Orthometopon romanicus, Armadillidium banaticum.